Analysis of the Philosophical Thought of the School of Isfahan in the Perspective of Sacred Science - Eksani; Agus Wahyu Triatmo (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
The philosophy of the School of Isfahan represents a pivotal intellectual movement within the Islamic tradition, offering an integration of reason, intuition, and revelation. This study aims to analyze the philosophical patterns of Isfahan thinkers, specifically Mulla Sadra, in establishing an epistemological foundation for spiritually-oriented knowledge through the lens of sacred science. This research employs a qualitative approach with a library research method. Data were gathered from both classical and modern literature, including the primary works of Seyyed Hossein Nasr, and subsequently analyzed using content analysis techniques. The findings indicate that the School of Isfahan positions reality as a hierarchical unity originating from God, where concepts such as the gradation of being (tasykik al-wujud) and substantial motion serve as the basis for understanding science as a means to attain ultimate truth. In contrast to modern science, which tends to be secular and materialistic, the perspective of sacred science in Isfahan asserts that nature consists of signs (ayat) reflecting Divine presence. This study concludes that the philosophy of the School of Isfahan contributes significantly to constructing an integrative and holistic paradigm of knowledge. Reconstructing this thought is essential for reviving an Islamic intellectual tradition capable of balancing the rational, empirical, and spiritual dimensions of humanity.